Digital Platform Skills for Teachers in Public Primary Schools in Homa Bay County, Kenya - Omito, Ouma Omito; Kembo, Jane Kembo (Journal of Education and Practice, 2022)
Purpose: The purpose of this study was to establish the readiness of headteachers and teachers in integrating Digital Literacy Programme (DLP) in teaching and learning in public primary schools in Homa Bay County, Kenya. Digital Literacy Programme was a project that was introduced and funded by the Government of Kenya for all public primary schools in Kenya. Methodology: The study adopted both qualitative and quantitative survey research designs. A population of 845 head teachers and 6529 teachers were involved in the study. Some 85 head teachers and 362 teachers were sampled for the study. Questionnaires and interviews were the main research instruments used for the study. The reliability coefficient for the piloted teachers stood at 0.96 while that of the head teachers' coefficient was reported at 0.95. The quantitative research data was analyzed using SPSS and presented in tables, frequencies and percentages. Interviews were recorded, transcribed, organized into main themes and reported. Findings: Majority of the respondents who were teachers, (41.6%), could only write using a digital device. Most head teachers, (34.2%), preferred tablets contrary to the preference of the majority of teachers, 31.4%, who cited desktop computers for online teaching and learning. The study also revealed that the majority of teachers and head teachers felt insecure with the digital devices in schools. Unique Contribution to Theory, Policy and Practice: Introduction of digital learning in the Kenyan education sector did not meet the required threshold but was timely. Challenges were met here and there. Both teachers and headteachers were struggling to cope with the modern teaching and methods that required the integration of technology in the teaching and learning process. However, with continuous practice, the digital gaps were set to close in Kenyan schools. In line with the Kenyan ICT Policy of 2006 on electronic learning, the promotion and development of content to address the educational needs of primary, secondary and tertiary institutions in Kenya needed to be emphasized.